Going Global? U.S. Government Policy and the Defense Aerospace Industry - Lorell, Mark A. (RAND Corporation, 2002)
The increasing consolidation of the defense aerospace industry, brought about by post-Cold War reductions in defense authorizations, has led to the proliferation of cross-border relationships between U.S. and European firms. This report examines aerospace industry globalization trends with a view toward determining how the U.S. Air Force can best exploit such trends while minimizing their risks. It concludes that further research must be done to ascertain how the advantages of globalization, such as increased competition and interoperability, can best be achieved without compromising security concerns.